Dyslexia: Disclaiming Reading Ability Langke Rembong District Primary School Level - Silaen, Dessi; Aprilia, Imas Diana (Angstrom Centre of Education, 2024)
This study aim For know and describe about data and existence child having difficulty learning, esp dyslexia in elementary school, via identification and assessment. Implementation identification and assessment as well as evaluation identification and assessment for child having difficulty Study This done in several Elementary School in District Langke Rembong, Regency Manggarai. Study This use method study descriptive with approach qualitative research conducted in several elementary schools in the district Langke Rembong, Regency Manggarai. Subject study that is student 5th grade in each school target. Data collection techniques use observation, interviews, identification and assessment. The validity of the data is tested use triangulation technique. Result of study This show that inside​ every school researched targets​ there is student having difficulty Study. Party school Not yet Once do assessment to students who experience difficulty Study. Student having difficulty Study still is at together other students study together inside​ class, not yet Once identified and assessed by the parties school nor from outside school. It is hoped that every school give handling special For children who experience disturbance Study.